2022
DOI: 10.1002/aet2.10728
|View full text |Cite
|
Sign up to set email alerts
|

“Everybody in this room can understand”: A qualitative exploration of peer support during residency training

Abstract: Objectives Though peer support groups are often utilized during residency training, the dynamics, content, and impact of social support offered through peer support are poorly understood. We explored trainee perceptions of the benefits, drawbacks, and optimal membership and facilitation of peer support groups. Methods After engaging in a peer support program at an emergency medicine residency program, 15 residents and 4 group facilitators participated in four focus groups in 2018. Interview questions explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Peer support programs provide a psychologically safe space to talk to an empathetic peer and help a resident process their error. 22,23 Peer supporters should undergo formal training to avoid the wellintentioned but ultimately unproductive tendencies to minimize the error or focus on rectifying the issue. 9 Peer supporters also need to develop effective listening, reflecting, and reframing skills as well as gain knowledge of resources and appropriate referrals.…”
Section: Formalize a Peer Re S P On S E Ne T Workmentioning
confidence: 99%
“…Peer support programs provide a psychologically safe space to talk to an empathetic peer and help a resident process their error. 22,23 Peer supporters should undergo formal training to avoid the wellintentioned but ultimately unproductive tendencies to minimize the error or focus on rectifying the issue. 9 Peer supporters also need to develop effective listening, reflecting, and reframing skills as well as gain knowledge of resources and appropriate referrals.…”
Section: Formalize a Peer Re S P On S E Ne T Workmentioning
confidence: 99%
“…A qualitative study conducted at our institution suggested that an additional barrier to effective communication between residents and their support persons (SP) is dissonance between residents’ personal and professional identities. 2 Residents encounter challenges discussing workplace stressors with individuals who have minimal understanding of the clinical environment. 1 , 2 Study authors recommended that future wellness interventions attempt to reduce this dissonance by proactively providing SPs with greater insight into the residency training experience.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Residents encounter challenges discussing workplace stressors with individuals who have minimal understanding of the clinical environment. 1 , 2 Study authors recommended that future wellness interventions attempt to reduce this dissonance by proactively providing SPs with greater insight into the residency training experience. 2 This recommendation is in line with existing literature highlighting the importance of social relatedness—engaging in meaningful conversation and feeling understood—in enhancing psychological well-being.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residents may seek support through peers or senior residents, and the peer relationship may be protective against burnout and improve recovery ( 26 , 27 ). Some institutional peer support programs provide a structure to offer residents support from other residents ( 25 ) and from recent graduates ( 24 ), describing benefits in normalizing the difficult experiences and allowing emotional and cognitive insight as they promote perceived well-being. However, residents face several barriers in becoming trained peer supporters because they may lack confidence to provide proactive intervention for their peers, and the demands of residency may limit the ability of residents to attend training or dedicate time to supporting coresidents ( 10 , 11 , 27 ).…”
mentioning
confidence: 99%